Reversal of 5-flouroucial resistance by adenovirus-mediated transfer of wild-type p53 gene in multidrug-resiatant human colon carcinoma LoVo/5-FU cells - Yu, Zhi-Wei (World J Gastroenterol, 2004)
AIM: To observe the reversal effects of wide-type p53 gene on multi-drug resistance to 5-FU (LOVO/5-FU). METHODS: After treatment with Ad-p53, LOVO/5-FU sensitivity to 5-Fu was investigated using tetrazolium dye assay. Multidrug resistance gene-1 (MDR1) gene expression was assayed by semi-quantitative reverse transcription-polymerase chain reaction and the expression of p53 protein was examined by Western blotting. RESULTS: The reversal activity after treatment with wide-type p53 gene was increased up to 4.982 fold at 48 h. The expression of MDR1 gene decreased significantly after treatment with wide-type p53 gene, and the expression of p53 protein lasted for about 5 d, with a peak at 48 h, and began to decrease at 72 h. CONCLUSION: Wide-type p53 gene has a remarkable reversal activity for the high expression of MDR1 gene in colorectal cancers. The reversal effects seem to be in a time dependent manner. It might have good prospects in clinical application.